The Landscape of Artificial Intelligence Ethics: Analysis of Developments, Challenges, and Comparison of Different Markets - Natrup, Simon (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management